Belonging and belongings: portable artefacts and identity in the civitas of the Iceni - Harlow, Natasha Pia (2018)
The Late Iron Age in northern East Anglia ends with the Boudican revolt in 60/61 CE, after which, the people known as the Iceni were subsumed by the Roman empire. This thesis tests the archaeological evidence for the Iceni as a defined group, demonstrated by the distinctive character material culture in the region. It investigates the theory that they were slow to adopt Roman imports and luxury goods, either as a form of deliberate resistance or due to cultural retardation following the Boudican revolt. It also questions the interpretive narrative of the Iceni as ‘Other’, in both Classical and modern sources. My research expands upon previous studies, which have often been restricted to a single county, time period, or class of artefact. It includes a broad study of the three counties most closely associated with the Iceni: Norfolk, Suffolk and Cambridgeshire. The chronological range (circa 100 BCE-200 CE) incorporates the Claudian invasion, Boudican rebellion and several generations either side. A large dataset of over 14,000 object records has been examined, drawn from county Historic Environment Records (HERs) and the Portable Antiquities Scheme (PAS). This project reassesses many of the long-held stereotypes about the Iceni in the light of the dramatic increases in metal-detector finds over the past 20 years. This thesis demonstrates that: • A single unified social entity (‘the Iceni’) is not archaeologically visible across the study area, although there is intra-regional patterning. • Iron Age modes of expressing status and identity persisted under Roman rule, through the manufacture, use and display of objects. • Evidence is lacking for regional impoverishment and depopulation in the aftermath of the Boudican revolt. • Metal-detected surface finds have significant research potential when viewed across a wide area and in conjunction with stratified sites.